Investigating Factors of Safety Culture Assessment in Construction Industry Projects - Tehrani, Vahid Zeinalabedin; Rezaifar, Omid; Gholhaki, Majid; Khosravi, Yahya (Civil Engineering Journal, 2019)
Early signs of an organizational commitment to safety policies are manifested in the safety culture in that organization. Improving the safety culture of contractors can reduce occupational accidents in construction industry projects. Many scholars tend to research on this concept in order to achieve an approach to reducing occupational accidents. Numerous studies have attempted to identify the components affecting the safety culture using various methods and tools for measuring and assessing the safety culture; nevertheless, none of these studies measured the impact level of each of the evaluated factors on the safety culture. Hence, this study, assess the influence of each of these factors on the safe culture of contractors working in the construction industry. This study used a structural equation modeling approach to examine the safety culture assessment factors. Accordingly, ten factors affecting the safety culture were scrutinized to provide a conceptual model with ten predictable paths for evaluating the relationships between the variables. The data collected from thermal power plant construction projects were applied to test the hypothesized model experimentally using SEM-PLS method. According to the results of this study, it can be concluded that the factors of management commitment, appraisal of work hazards, supportive environment and communication among the factors influencing the safety culture of contractors in the studied projects had respectively the most impact on the safety culture of contractors operating in the thermal power industry, as well as the work pressure had the least impact on the safety culture..